RESISTANCE OF POTATO HYBRIDS FROM THE SECOND TUBER GENERATION TO THE LOCAL POPULATION OF PHYTOPHTHORA INFESTANS (MONT.) DE BARY AND SELECTION OF ADVANCED CLONES - Z. Z. Evdokimova; M. V. Kalashnik (Труды по прикладной ботанике, генетике и селекции)
Interspecific potato hybrids of various origins were analysed in the field under a strong Phytophthora infestans (Mont.) de Bary invasion  in the epidemic 2016 and 2017 seasons for foliar and tuber  resistance to late blight. Clones of the second generation were  assessed for their productivity and tuber quality. Genotypes with the  highest resistance to late blight were selected within the populations derived from the following cross combinations: 'Svitanok  Kievsky' x 96133/16, 9451/9 x 94110/8, 943/6 x 'Gitte',  9685/1 x 943/9, 'Sudarynya' x 9674/38, 'Charodey' x 943/9, 'Skarb'  x 94155/1, 'Charodey' x 91102/12 as well as in the progeny  obtained after self-pollination of the varieties: 'Udacha', 'Charodey',  'Bravo', 'Amur', 'Vektar', 'Cortney', 'Yanka', 'Zhuravinka', 'Frittella', 'Real', 'Matushka', 'Irbitsky', and accessions K-22890, 28- 06 and 85-06. Analysis of late blight resistance at early stages of the breeding process increases informativity and helps to identify  promising accessions with different field resistance levels and a set  of economically valuable traits. As a result of this research, genotypes with increased productivity and good table  quality of tubers were selected among the material possessing high  and medium resistance to the pathogen. Original hybrids will be  used as source material in the breeding programs targeted at the  development of cultivars with field resistance to late blight. There  are plans to continue and improve breeding work with such  accessions in the context of their resistance to other diseases and  environmental stress factors.